Implementasi Literasi Budaya dan Kewargaan Melalui Program LEKSAM BEDAS di SDN Cipaku 03 Untuk Meningkatkan Kreativitas Pada Siswa - Ridha Haifarashin; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research aims to determine the implementation of cultural and civic literacy through the LEKSAM BEDAS literacy program at SDN Cipaku 03 to increase creativity in students. This research uses one method, namely the qualitative descriptive method. Then the researcher also studied research information from the results of interviews conducted with the fifth grade teacher who was the literacy program supervisor at SDN Cipaku 03. Data collection techniques were carried out using observation, interviews and documentation. Data analysis was carried out using data collection, data reduction, data presentation, inference and verification techniques. The results of the research show that SDN Cipaku 03 has implemented the Family Educational Literacy program, Children’s School and Community, Awakening to Dynamic, Prosperous, Religious Education (Leksam Bedas) in order to improve literacy and creativity skills in students. The Bedas Leksam program can be carried out by utilizing libraries and other reading areas as literacy infrastructure that supports students. The Bedas Leksam program can be combined with cultural literacy and civic literacy.